The Promising Role of Speckle-tracking Echocardiography in Detecting the Patchy Nature of Myocarditis, Insights from Case Series in the Largest Pediatrics Tertiary Center of UAE - Antoine Fakhry AbdelMassih; Arshad Khan; Zahra Majichian; Afnan Musleh; Ashutosh Goyal; Sara M. AlDarmaki (Heart Views)
There is increasing evidence that myocarditis starts as a patchy process, accordingly, the detection of segmental affection is important for early recognition of the disease and proper initiation of anti-inflammatory treatment. We present our first experience here with using speckle-tracking echocardiography (STE) to detect subtle segmental involvement of the left ventricle in two cases with suspected myocarditis. STE consolidated the diagnosis and helped with the early initiation of intravenous immunoglobulins and subsequent control of the disease. STE was also able to show the specific topography of distribution of each pathogen linked to inflammation.